2018
DOI: 10.1080/03054985.2017.1421153
|View full text |Cite
|
Sign up to set email alerts
|

Inequality of educational opportunity: the relationship between access, affordability, and quality of private schools in Lagos, Nigeria

Abstract: Using data from a census of private schools in one of Lagos, Nigeria's administrative jurisdictions, this paper explores the linkages between a heterogeneous sector of private schools and issues of school access, affordability, quality, and ultimately social mobility for households at the bottom of the income distribution. Although a large private education market has buoyed Lagos's growth towards near-universal primary enrolment, this heterogeneous school sector appears to be providing socially stratifying pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Nevertheless, this finding has shown that intervention programs should be targeted at private schools if the reduction of the prevalence of behavioral disorders in Nigeria is anticipated. Despite the perceived advantages of private education [149,150], parents are to be aware that sending their wards there would not shield them from externalizing behavior unless a targeted action is taken to address disruptive behavior observed in them. Even religious private schools are not exceptions [151].…”
Section: School Type and The Trio Of Aggression Delinquency And Hyperactivitymentioning
confidence: 99%
“…Nevertheless, this finding has shown that intervention programs should be targeted at private schools if the reduction of the prevalence of behavioral disorders in Nigeria is anticipated. Despite the perceived advantages of private education [149,150], parents are to be aware that sending their wards there would not shield them from externalizing behavior unless a targeted action is taken to address disruptive behavior observed in them. Even religious private schools are not exceptions [151].…”
Section: School Type and The Trio Of Aggression Delinquency And Hyperactivitymentioning
confidence: 99%
“…Public-sector teachers are classified as civil servants and thus receive guaranteed remuneration levels and job security, while private-sector teachers are generally paid less with no job security (Osei, 2006). Importantly, a large majority of private schools in Ghana charge low fees and cater to low-income families (known as lowfee private schools), and many struggle to cover their costs (Baum, Abdul-Hamid, & Wesley, 2018). Yet, parents often perceive them to be of better quality than public schools (Dixon & Tooley, 2012;Zuilkowski, Piper, Ong'ele, & Kiminza, 2018).…”
Section: Public Versus Private Schoolsmentioning
confidence: 99%
“…Importantly, a large majority of private schools in Ghana charge low fees and cater to low‐income families (known as low‐fee private schools), and many struggle to cover their costs (Baum, Abdul‐Hamid, & Wesley, ). Yet, parents often perceive them to be of better quality than public schools (Dixon & Tooley, ; Zuilkowski, Piper, Ong’ele, & Kiminza, ).…”
Section: Introductionmentioning
confidence: 99%
“…This is due to the fact that rapid and exponential costs of higher education raise a key question of how HEIs should be funded. According to Baum et al (2018), many governments are to meet the demand for expanding welfare programs and are either unenthusiastic or averse to spending public resources on HEIs due to financial limitations. There is also the critical issue of regulation that is necessary for the rapidly expanding and diversifying higher education sector.…”
Section: Discussionmentioning
confidence: 99%
“…Giving the large pool of potential workers in sub-Saharan African countries, education may also influence employment decisions (Baum et al 2018). This view is maintained by who demonstrated from their research that having a secondary education improves access to the job market, with the probability of employment further improving with tertiary education.…”
Section: Inequality In African Educational Systemsmentioning
confidence: 99%